Neuro-hormonal Regulation Is a Better Indicator of Human Cognitive Abilities Than Brain Anatomy: The Need for a New Paradigm - Saniotis, Arthur; Grantham, James P.; Kumaratilake, Jaliya; Henneberg, Maciej (Frontiers in Neuroanatomy, 2020)
Human intelligence has been theorised since the ancient Greeks. Plato and Aristotle incorporated theories of human intelligence into their metaphysical and cosmological theories which informed the social and medical sciences for centuries. With the advent of the 20th century, human intelligence became increasingly standardised based on Intelligence Quotients (IQ). Moreover, multiple theories of human intelligence were posited on morphological features of the human brain, focusing on cranial volume and size of the pre-frontal cortex which was suggestive of superior human cognitive abilities. This paper argues that fixation with anatomical features of the brain was tended to ignore the importance of neuro-hormonal regulation which is a more appropriate indicator of human cognitive abilities. The article challenges the correlation between brain size and human cognitive abilities while offering and alternate theory of human cognitive abilities which emphasises the roles of neurotransmitters, neurotrophins and Enteric Gut Microbiome regulation.